Individual and combined effects of heat and drought and subsequent recovery on winter wheat (Triticum aestivum L.) photosynthesis, nitrogen metabolism, cell osmoregulation, and yield formation - Ru, Chen (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.